Narrative Methods vol. II Narrative applications - Delamont, Sara; Atkinson, Paul (London, Thousand Oaks, New Delhi : Sage Publications, 2006)
Atkinson, Paul - Silverman, David - Kundera's immortality : the interview society and the invention of the self
Kendall, Lori - Meaning and identity in "cyberspace" : the performence of gender, class, and race online
Edvardsson, David - Rasmussen, Birgit Holritz - Riessman, Catherine Kohler - Ward atmospheres of horror and healing : a comparative analysis of narrative
Bennett, Kate Mary - Vidal-Hall, Steph - Narratives of death : a qualitative study of widowhood in later life
Norrick, Neal R. - Humor, tellability, and conarration in conversational storytelling
Wortham, Stanton - Interactional positioning and narrative self-construction
Hänninen, Vilma - A model of narrative circulation - Baynham, Mike - Narratives in space and times : beyond "backdrop" accounts of narrative orientation
Cary, Lisa J. - Unexpected stories : life history and the limits of representation
Gudmundsdottir, Sigrun - The teller, the tale, and the one being told : the narrative nature of the research interview
Brown, Gavin - Listening to queer maps of the city : gay men's narratives of pleasure and danger in London's East End
Day Sclater, Shelley - The "bubble that burst" : Jane's divorce story
Crossley, Michele L. - "Survivors" and "victims" : long-term HIV posive individuals and the ethos of self-empowerment
Ezzy, Douglas - Illness narratives : time, hope and HIV
Lather, Patti A. - The validity of angels : interpretative and textual strategies in researching the lives of women with HIV/AIDS
Atkinson, Paul - Narrative turn or blind alley ?
Gwyn, Richard - "Really unreal" : narrative evaluation and the objectivation of experience
Notes, bibliogr. dissém.
0017